2016
DOI: 10.3390/molecules21101326
|View full text |Cite
|
Sign up to set email alerts
|

Saponins from Chinese Medicines as Anticancer Agents

Abstract: Saponins are glycosides with triterpenoid or spirostane aglycones that demonstrate various pharmacological effects against mammalian diseases. To promote the research and development of anticancer agents from saponins, this review focuses on the anticancer properties of several typical naturally derived triterpenoid saponins (ginsenosides and saikosaponins) and steroid saponins (dioscin, polyphyllin, and timosaponin) isolated from Chinese medicines. These saponins exhibit in vitro and in vivo anticancer effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(106 citation statements)
references
References 210 publications
(279 reference statements)
1
95
0
Order By: Relevance
“…Saponins, secondary metabolites of plants, are glycosides of triterpenoid or steroidal aglycones which exhibit various biological activities including anti-inflammatory, antioxidant, and antimicrobial (Guclu-Ustundag & Mazza, 2007). Saponins such as ginsenoside and saikosaponin were found to exhibit anticancer activity (Xu et al, 2016). In addition, saponins were found to improve the pathology of neurological disorders, including Alzheimer's disease and Parkinson's disease (Sun, Xu, Lin, Cui, & Xu, 2015).…”
Section: Saponinsmentioning
confidence: 99%
“…Saponins, secondary metabolites of plants, are glycosides of triterpenoid or steroidal aglycones which exhibit various biological activities including anti-inflammatory, antioxidant, and antimicrobial (Guclu-Ustundag & Mazza, 2007). Saponins such as ginsenoside and saikosaponin were found to exhibit anticancer activity (Xu et al, 2016). In addition, saponins were found to improve the pathology of neurological disorders, including Alzheimer's disease and Parkinson's disease (Sun, Xu, Lin, Cui, & Xu, 2015).…”
Section: Saponinsmentioning
confidence: 99%
“…The early-apoptotic phenomenon of MCF-7/ADR was promoted by the combination of pristimerin and doxorubicin [26]. Ginsenoside Rg3 enhanced the intrinsic cell apoptosis pathway of cyclophosphamide to delay the tumor growth in hepatocellular cancer cell line Hep1-6 inoculated mice and prolong their lifespan [27,28]. Herein, ZA-A helped paclitaxel arrest KB/VIN at cell cycle G2/M phase and promote apoptosis; however, whether the apoptosis is related to intrinsic or extrinsic apoptotic pathways still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Modern phytochemical and pharmacological research showed that the genus Paris had anti-tumor effects and steroidal saponins were the chief active components. For example, Polyphyllin I (D), Polyphyllin II, Polyphyllin III, Polyphyllin VII and paris saponin H, which were isolated from Paris, have significant anti-cancer effects, including ovarian cancer, liver cancer, stomach cancer, colon cancer, breast cancer, osteosarcoma, melanoma and glioblastoma (18,19). Liu et al reported Polyphyllin I induced G2/M phase arrest and apoptosis in U251 human glioblastoma cells via JNK signaling pathway (20).…”
Section: Introductionmentioning
confidence: 99%